2022
DOI: 10.1371/journal.pone.0273678
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-associated lactic acidosis and factors associated with 30-day mortality

Abstract: Background Metformin-associated lactic acidosis (MALA) is a rare event but underrecognition may lead to unfavorable outcomes in type 2 diabetes patients. While many risk factors of MALA have been identified, how to reduce mortality from MALA is a matter of debate. This study aimed to explore the factors associated with 30-day mortality amongst MALA patients. Methods An observational study enrolled patients diagnosed with MALA between January 2014 and December 2017. MALA was defined by a history of metformin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…[ 25 ] Not surprisingly, an observational study of 105 patients with MALA reported that a lower APACHE II score and time to dialysis (<6 h) are associated with lower 30-day mortality. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Not surprisingly, an observational study of 105 patients with MALA reported that a lower APACHE II score and time to dialysis (<6 h) are associated with lower 30-day mortality. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Metformin associated lactic acidosis can occur at therapeutic doses in adults or in overdose, and it usually occurs in older patients with acute kidney injury or chronic kidney disease, with dehydration, and sepsis. 14 , 15 It is rarely reported in children.…”
Section: Discussionmentioning
confidence: 99%
“…59 Lactic acidosis and dialysis treatment within 6 h after admission were independently associated with lower 30-day mortality. 60 Unexpectedly, some evidence suggests that mortality for lactic acidosis is not predicted by metformin dose or levels, 61 and may be even reduced in subjects consuming higher metformin doses. 62 The ALIMAR-C2 study, announced in 2019, should assess the association between metformin use and lactic acidosis in PwD and impaired kidney function through the evaluation of health records from eight Spanish hospitals linked to their corresponding primary care health areas, comprising approximately 22.1 million person-years of followup.…”
Section: Tolerability and Dose-dependent Side Effectsmentioning
confidence: 99%
“…In metformin‐treated PwD admitted in an emergency context, a plasma metformin concentration ≥ 9.9 mg/L was strongly associated with lactic acidosis 59 . Lactic acidosis and dialysis treatment within 6 h after admission were independently associated with lower 30‐day mortality 60 . Unexpectedly, some evidence suggests that mortality for lactic acidosis is not predicted by metformin dose or levels, 61 and may be even reduced in subjects consuming higher metformin doses 62 .…”
Section: Tolerability and Dose‐dependent Side Effectsmentioning
confidence: 99%